Chapter 12: Crossing Borders to Target Al-Qaeda and Its Affiliates: Defining Networks as Organized Armed Groups in Non-International Armed Conflicts. (2nd February 2015) - Margulies, Peter; Sinnot, Matthew
Abstract: Al-Qaeda's dispersal and the rise of regional terrorist groups such as Al-Shabaab in Somalia have raised the stakes for defining an "organized armed group" (OAG). If an entity fails the OAG test, a state may use only traditional law enforcement methods in responding to the entity's violence. Both case law and social science literature support a broadly pragmatic reading of the OAG definition. While the International Criminal Tribunal for the former Yugoslavia (ICTY) has cited factors such as existence of a headquarters and imposition of discipline, ICTY decisions have found organization when evidence was at best equivocal. Moreover, terrorist organizations reveal surprisingly robust indicia of organization. Illustrating this organizational turn, a transnational network like Al-Qaeda operates in a synergistic fashion with regional groups. Moreover, recent news reports have suggested that current Al-Qaeda leader Dr. Ayman al-Zawahiri has attempted to assert operational control over the specific targeting decisions of Al-Qaeda affiliates, although that effort has not been uniformly successful. Furthermore, while Al-Qaeda does not micromanage most individual operations, it exercises strategic influence, e.g., through a focus on targeting Western interests. When such strategic influence can be shown, the definition of OAG is sufficiently flexible to permit targeting across borders. In addition, the doctrine of co-belligerency, borrowed from neutrality law, provides a basis for targeting that is not confined by state boundaries. Even when these indicia are absent, individuals within non-Al-Qaeda groups may be targetable if they engage in coordinated activity with Al-Qaeda.